Novel Approaches to Forensic Explosives Recovery, Storage and Analysis - Yu, Holly April (Curtin University, 2017)
This thesis describes a series of studies aiming to improve current practices associated with forensic explosives recovery, storage and analysis. Specifically, fundamental studies on the recovery of explosives from textiles and the storage of soil samples containing explosives were performed. A novel electrochemical technique for the detection of TNT was also developed.